The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.17305/bjbms.2010.2730
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Changes in the Liver of Intravenous Heroin Addicts

Abstract: The ultrastructural research has a decisive role in gathering the knowledge on the liver's response to the influence of some drugs. The aim of the study was to perform an ultrastructural analysis of the liver in chronic intravenous heroin addicts.The study involved the autopsy conducted on 40 bodies of intravenous heroin addicts and 10 control autopsies. The liver tissue was fixed in glutaraldehyde and moulded with epon for investigation purposes of ultrastructural changes. The analysis was performed using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The literature data for the morphological changes and severity of liver damage in HA patients with CHC on liver biopsies are scanty. In contrast, in several studies the light microscopic and ultrastructural changes in liver autopsy samples of intravenous heroin addicts have been reported (18)(19)(20)(21)(22). The authors summarized that heroin abuse induces significant morphologic changes in the liver tissue, including vesicular and fatty changes, reduction in the amount of glycogen in hepatocytes, chronic hepatitis, cirrhosis and the severity of these changes increases with years of heroin abuse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature data for the morphological changes and severity of liver damage in HA patients with CHC on liver biopsies are scanty. In contrast, in several studies the light microscopic and ultrastructural changes in liver autopsy samples of intravenous heroin addicts have been reported (18)(19)(20)(21)(22). The authors summarized that heroin abuse induces significant morphologic changes in the liver tissue, including vesicular and fatty changes, reduction in the amount of glycogen in hepatocytes, chronic hepatitis, cirrhosis and the severity of these changes increases with years of heroin abuse.…”
Section: Discussionmentioning
confidence: 99%
“…The heroin addicted subjects are the main risk group for infection with hepatitis C virus (HCV). In literature various pathological changes in the livers of heroin abusers have been reported (18)(19)(20)(21)(22). They included quantitative and qualitative alterations of cellular organelles, extracellular matrix and hepatic vascular system like vacuole and fatty degeneration, changes in the cellular nucleus, membranes or intracellular content of glycogen, inflammation, fibrosis/cirrhosis, dysplasia, amyloidosis.…”
Section: Introductionmentioning
confidence: 99%
“…Using the method of transmission electron microscopy, the ultrastructural findings in the liver of intravenous heroin addicts were characterised by the hyperplasia and hypertrophy of the smooth endoplasmic reticulum, the vesicular degeneration of hepatocytes occurring as a result of the increased synthesis of the enzymes of the smooth endoplasmic reticulum, and the presence of a continuous basal membrane accompanied by the transformation of sinusoids into capillaries, leading to the impaired microcirculation that can ultimately progress in cirrhosis [ 108 ].…”
Section: Liver Damage By Some Illicit Drugsmentioning
confidence: 99%
“…A study involving autopsies in 40 heroin addicts demonstrated hyperplasia and hypertrophy of the smooth endoplasmic reticulum, but these were chronic users many with chronic active hepatitis [10]. …”
mentioning
confidence: 99%